Communist parties revisited : sociocultural approaches to party rule in the Soviet bloc, 1956-1991 - Bergien, Rüdiger; Gieseke, Jens (Berghahn Books, 2018)
"The ruling communist parties of the postwar Soviet Bloc possessed nearly unprecedented power to shape every level of society; perhaps in part because of this, they have been routinely depicted as monolithic, austere, and even opaque institutions. Communist Parties Revisited takes a markedly different approach, investigating everyday life within basic organizations to illuminate the inner workings of Eastern Bloc parties. Ranging across national and transnational contexts, the contributions assembled here reconstruct the rituals of party meetings, functionaries' informal practices, intra-party power struggles, and the social production of ideology to give a detailed account of state socialist policymaking on a micro-historical scale"-- Provided by publisher.
Keywords: Communist parties -- Europe, Eastern -- History -- 20th century.; Communist parties -- Communist countries -- History.; Communism -- Soviet Union -- History -- 20th century.; Europe, Eastern -- Social conditions -- 20th century.; Europe, Eastern -- Politics and government -- 20th century.; Communist countries -- Social conditions -- 20th century.; Communist countries -- Politics and government -- 20th century.; Partis communistes -- Europe de l'Est -- Histoire -- 20e siècle.; Partis communistes -- Pays socialistes -- Histoire.; Communisme -- URSS -- Histoire -- 20e siècle.; Europe de l'Est -- Conditions sociales -- 20e siècle.; Europe de l'Est -- Politique et gouvernement -- 20e siècle.; Pays socialistes -- Conditions sociales -- 20e siècle.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; HISTORY / Europe / Russia & the Former Soviet Union; Social conditions; Politics and government; Communist parties; Communism; Eastern Europe; Communist countries; Soviet Union; 1900-1999; History